Benefits of Interactive Whiteboards for Teachers and Students (Journal of Pedagogical Inventions and Practices, 2022)
This article is deals with the problems of teaching and the importance of interactive whiteboards. This article mainly focuses on using interactive whiteboards, materials of the lesson, the role of teachers and students in classroom.